2011
DOI: 10.1364/ol.36.003479
|View full text |Cite
|
Sign up to set email alerts
|

Nondiffracting transversally polarized beam

Abstract: Generation of a nondiffracting transversally polarized beam by means of transmitting an azimuthally polarized beam through a multibelt spiral phase hologram and then highly focusing by a high-NA lens is presented. A relatively long depth of focus (∼4.84λ) of the electric field with only radial and azimuthal components is achieved. The polarization of the wavefront near the focal plane is analyzed in detail by calculating the Stokes polarization parameters. It is found that the polarization is spatially varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 12 publications
0
46
1
2
Order By: Relevance
“…Generally a double-ring-shaped azimuthally polarized beam without any phase modulation is tightly focused, a single-ring focal hole pattern is obtained (Lalithambigai et al 2013). It is reported that using SPM with a high NA lens one can generate a single transversely polarized bright focal spot (Yuan et al 2011). Hence, in order to generate bright spot in the focal region, we need an SPM with a high NA lens system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally a double-ring-shaped azimuthally polarized beam without any phase modulation is tightly focused, a single-ring focal hole pattern is obtained (Lalithambigai et al 2013). It is reported that using SPM with a high NA lens one can generate a single transversely polarized bright focal spot (Yuan et al 2011). Hence, in order to generate bright spot in the focal region, we need an SPM with a high NA lens system.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also confirmed that the azimuthally polarized beam phase encoded by a vortex 0-2π phase would produce a considerably sharper focal spot on the focal region (Hao et al 2010). More recently, the generation of a non diffracting transversally polarized beam have the long DOF (4.84 λ) with sub diffraction spot size (0.53 λ) by highly focusing an azimuthally polarized beam with a high NA lens and a multibelt spiral phase hologram is established numerically (Yuan et al 2011). Another study, a subwavelength transversally polarized beam have the spot size (0.384 λ) with a longer DOF (over 11.454 λ) has been generated using high NA lens axicon with multibelt phase modulation (Suresh et al 2013).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…By replacing the 532-nm incident wavelength with λ = 633 nm, we managed to obtain [11] a tighter focal spot of size FWHM = (0.40 ± 0.02)λ using the same microlens. Publications concerned with the subwavelength focusing of radially and azimuthally polarized laser beams have also been widely known [12][13][14][15]. Focal spots of size FWHM = 0.43λ (NA = 0.95) [12,14], FWHM = 0.30λ (NA = 1.4) [13] have been obtained in the numerical and physical experiments.…”
Section: Introductionmentioning
confidence: 99%